Narrativas de pais sobre meninas com Transtorno do Déficit de Atenção e Hiperatividade: um estudo sob o enfoque sistêmico - Pereira, Ana Leticia Guedes (2012)
In recent years, complaints about Attention Deficit Disorder and Hyperactivity became frequent services to destinations child and adolescent population. This disorder is also presented by adults and impairs the academic, professional and staff who present it. Although they have many strengths, people with ADHD can be put in place a number of problems in the environments they frequent. And it is noteworthy that there are studies that demonstrate the existence of comorbidities related to the disorder in question. Based on the facts presented above, research on the subject are essential to enhance understanding about it. This research aimed to verify the existence of similarities and differences in the design of the parents in relation to ADHD, specifically to verify the existence of factors related to the dynamics between parents and children that could be contributing to the maintenance of the difficulties experienced and the existence of alternative used by the family to minimize these difficulties. To this end, this research adopted a qualitative design and is based on the systemic approach, participants were two sets of parents with children who have complaints of ADHD. To collect data we used a semi-structured interview, dealing with the issue. The results showed that parents differ little about ADHD. And that among the alternative coping adopted the recurrence of professionals working on the subject and finding information, using instruments such as the Internet, strategies are chosen by parents. Through analysis of the collected material was observed that at times during the trajectory family responsibility dimension of each of the difficulties faced, remained forgotten and because some member of this family was placed in a position crystallized within the family. On the other hand the existence of family myths and communication difficulties disrupted the relationship between parents and children